Exploring Islamic Insurance (Takaful) Efficiency in Scientific Literatures - Nurul Izza, Nadia; Devi, Abrista (Journal of Islamic Economics Literatures, 2023)
This study attempts to map research related to the efficiency of Takaful (Sharia Insurance) published by Dimensions.ai indexed journals from 2010 to 2022. NVivo 12 Plus is used to conduct thematic studies and the frequency is used to evaluate 56 publications in scientific literature. The results of the study found that the number of publications fluctuated from year to year related to Takaful efficiency research which indicated that this topic was an interesting topic and should continue to be developed. In addition, various focus discussions and cluster analysis that describe the research paths in Takaful efficiency research include (1) Cost efficiency in the takaful industry, (2) Comparison of the efficiency levels of takaful and conventional insurance, (3) Islamic insurance from a macro (industry) perspective. This research can be used as a starting point for experts to build graphical visualizations of Takaful efficiency research patterns in published scientific research.